IEEE International Conference on Software - Science, Technology &Amp; Engineering (SwSTE'05) 2005
DOI: 10.1109/swste.2005.9
|View full text |Cite
|
Sign up to set email alerts
|

CarCoach: a generalized layered architecture for educational car systems

Abstract: Car accidents are a major concern. Consequently, a lot of research is carried out on car user interfaces. For each such research, usually a special simulator or car is developed, algorithms and tools are redeveloped, and similar issues arise. We propose CarCoach, an educational car system, based on a generalized layered architecture. We present the system design, the intelligent modular architecture, its layers, including details of some of its relevant modules. Using the Chrysler 300M IT-Edition car as a plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The CarCoach project by Sharon, Selker, Wagner, and Frank (2005), for example, used a broad range of sensors, such as cameras, pressure sensors, GPS, and information provided by the car (e.g. gear and turn signal state), to track the behaviour of the driver.…”
Section: Automotive Behaviour Change Support Systemsmentioning
confidence: 99%
“…The CarCoach project by Sharon, Selker, Wagner, and Frank (2005), for example, used a broad range of sensors, such as cameras, pressure sensors, GPS, and information provided by the car (e.g. gear and turn signal state), to track the behaviour of the driver.…”
Section: Automotive Behaviour Change Support Systemsmentioning
confidence: 99%
“…CarCoach uses numerous sensors, like cameras and pressure sensors, to provide immediate feedback on incidents like not looking at the road or being distracted by handling the radio while driving. However, Sharon et al (2005) showed that negative feedback from the system is easily perceived as frustrating. And there is also always a risk that the feedback itself is a further distraction, when given immediately.…”
Section: Automotive Behaviour Change Support Systemsmentioning
confidence: 99%
“…Products such as the Onstar system introduced in 1995 that works with an automotive network, GPS and a communication network to aid drivers, show the beginning of the convergence of heterogeneous sensor-driven services for human needs [58]. Demonstration systems that use the convergence of data from heterogeneous sources [59] [60,61], demonstrated that a system can recognize and encourage a person to reduce driving errors by simply watching the speed, steering wheel, gas, brake, cup holder and blinkers.…”
Section: Context-aware Computingmentioning
confidence: 99%